Bacteriological and Physicochemical Water Quality of Four Ponds of Dhaka Metropolis (Bangladesh Journal of Botany, 2012)
The aerobic heterotrophic bacterial count of four pond water samples ranged between 6.92×104 and 1.72×106cfu/100 ml. The highest count (1.72×106 cfu/100 ml) was recorded in Zahurul Haq Hall pond water.Enteric bacterial count was found in between 1.69×104 and 3.31×105 cfu/100ml in water samples. A total of 79 isolates were obtained of which 24 were randomly selected for further study. Among them Bacillus, Micrococcus and Planococcus were Gram-positive, while Escherichia, Enterobacter and Klebsiella were Gram-negative. Physicochemical parameters of the ponds satisfied water quality standards except NH4+-N. Among the ponds, CODCr and BOD5 values of the water samples were 18.29-19.75 mg/l and 3.18-6.05 mg/l, respectively. Most of the Gram negative bacteria were found to be multi drug resistant. DOI: http://dx.doi.org/10.3329/bjb.v41i1.11083 Bangladesh J. Bot. 41(1): 55-60, 2012 (June)